ARTHROSCOPIC CHARACTERISTICS OF ROTATOR CUFF TEARS AT HA DONG GENERAL HOSPITAL (2023-2025) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the characteristics of rotator cuff tears on arthroscopy in patients undergoing arthroscopic rotator cuff repair at Ha Dong General Hospital from June 2023 to June 2025. Methods: A study was conducted on 25 patients who underwent surgical treatment for rotator cuff tears at the Department of Trauma and Orthopedics, Ha Dong General Hospital, between June 2023 and June 2025. Results: The study of 25 cases revealed that 100% of the patients had supraspinatus tendon lesions, frequently associated with a curved (48%) or hooked (40%) acromion morphology, alongside concomitant injuries such as labral tears or biceps tendon pathologies. Regarding the morphological characteristics, the majority were C-shaped tears (68%), with tendon retraction and fatty degeneration predominantly classified as grade II. Following arthroscopic tendon repair, shoulder joint function improved significantly, with the mean UCLA score reaching 30.28 (p=0.001). Statistical analysis also indicated that the initial postoperative clinical outcomes showed no significant differences. Conclusion: Rotator cuff lesions treated with arthroscopic repair exhibit characteristic features, being almost exclusively localized to the supraspinatus tendon, primarily presenting as C-shaped tears with grade II tendon retraction and fatty degeneration. Arthroscopic rotator cuff repair demonstrates high therapeutic efficacy, achieving a mean UCLA score of 30.28 at 6 weeks postoperatively. Initial observations indicate no statistically significant difference in postoperative shoulder functional outcomes among different lesion types (potentially due to the small sample size).
Keywords: Rotator cuff tear, arthroscopic shoulder surgery, shoulder MRI.